Integrating Project-Based Green Education Learning in Environmental Chemistry Courses: An Innovative Strategy to Foster 21st-Century Skills and Digital Literacy of Pre-Service Chemistry Teachers - Sumanik, Novike Bela; Indrawati, Nenny; Nurhidayah; Uspayanti, Rezky; Jua, Selestina Kostaria; Asmaningrum, Henie Poerwandar; Sumanik, Ermy Dikta (The Indonesian Institute of Science and Technology Research, 2026)
The digital era requires pre-service teachers to possess digital literacy that is integrated with environmental awareness values. A crucial issue that emerges is the limited ability of pre-service chemistry teachers to combine critical thinking, creativity, collaboration, and communication with digital technology skills to address environmental problems innovatively. Previous studies have demonstrated the effectiveness of Project-Based Learning (PjBL) in enhancing 21st-century skills; however, a research gap remains in integrating green education values with strengthened digital literacy within the context of environmental chemistry learning. This study aimed to analyze the effectiveness of integrating YouTube-based PjBL with a Green Education approach in improving 21st-century skills and digital literacy among pre-service chemistry teachers. This research employed a mixed-methods sequential explanatory design, beginning with quantitative data collection through pretest–posttest, followed by qualitative data obtained through interviews, observations, and document analysis. The test instruments measured 21st-century skills and digital literacy, while video project quality was evaluated using a rubric, with two raters. The results show a significant increase in 21st-century skills with an N-gain of 0.71 (high category), and an increase in digital literacy with an N-gain of 0.64 (medium category) across all dimensions, particularly in digital communication and collaboration. Video project assessments indicated good quality with an average score of 85.24. Qualitative data reinforced the quantitative findings, revealing that YouTube-based PjBL fosters meaningful learning, enhances creativity, technological competence, and environmental awareness. This study implies that digital PjBL has the potential for broader implementation in chemistry education to strengthen 21st-century competencies.